Case Report: Adenosine kinase deficiency diagnosed 10 years after liver transplantation: Novel phenotypic insights - Lipiński, Patryk; Ciara, Elżbieta; Jurkiewicz, Dorota; Pronicki, Maciej; Jurkiewicz, Elżbieta; Bogdańska, Anna; Płoski, Rafał; Jankowska, Irena (Frontiers in Pediatrics, 2022)
Adenosine kinase (ADK) deficiency is a rare inborn error of methionine and adenosine metabolism. So far, a total of 27 patients with ADK deficiency have been reported. Here, we describe the first Polish patient diagnosed with ADK deficiency, aiming to highlight the clinical presentation of disease, emphasize diagnostic difficulties, and report the long-term follow-up. Six-month-old patient presented with cholestatic liver disease, macrocytic anemia, developmental delay, generalized hypotonia, delayed brain myelination, and elevated levels of serum methionine. A decrease of mitochondrial respiratory chain complex II and III activity were found in the postnuclear supernatants obtained from skeletal muscle biopsy. The patient underwent living-donor liver transplantation (LTx) at 14 months of age. Ten-year follow-up after LTx revealed a preserved good liver function, persistent regenerative macrocytic anemia, progressive neurological disease but disappearance of brain MR changes, short stature, and cortisol deficiency. Whole exome sequencing revealed the patient to be affected with two novel ADK variants, which pathogenicity was confirmed biochemically by demonstration of elevated concentration of S-adenosylhomocysteine.